2021
DOI: 10.1021/acs.macromol.0c01691
|View full text |Cite
|
Sign up to set email alerts
|

Arresting Elevated-Temperature Creep and Achieving Full Cross-Link Density Recovery in Reprocessable Polymer Networks and Network Composites via Nitroxide-Mediated Dynamic Chemistry

Abstract: Thermosets and thermoset composites constitute an extraordinary challenge for recycling and participation in a circular economy because their permanent covalent cross-links prevent spent thermosets from being melt processed into new products. With annual world-wide production in the tens of billions of kilograms, the inability to recycle thermosets into high-value products represents major economic and sustainability losses. While recent research into polymer networks with dynamic covalent cross-links has indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 105 publications
3
64
0
Order By: Relevance
“…This is in line with reported studies, which showed that a synergetic effect is typically observed when multiple dynamic chemistries are implemented in a material. , Besides, when stress relaxation experiments were performed at different temperatures for the obtained materials, a high temperature dependence was observed, resulting in a flow activation energy ( E a(flow) ) of 110–240 kJ mol –1 (Table ). Such high temperature dependent dynamic behavior favors the creation of dynamic, yet creep resistant elastomers, as very recently reported with addition-type reprocessable elastomers …”
Section: Resultsmentioning
confidence: 53%
“…This is in line with reported studies, which showed that a synergetic effect is typically observed when multiple dynamic chemistries are implemented in a material. , Besides, when stress relaxation experiments were performed at different temperatures for the obtained materials, a high temperature dependence was observed, resulting in a flow activation energy ( E a(flow) ) of 110–240 kJ mol –1 (Table ). Such high temperature dependent dynamic behavior favors the creation of dynamic, yet creep resistant elastomers, as very recently reported with addition-type reprocessable elastomers …”
Section: Resultsmentioning
confidence: 53%
“…It is known that a higher temperature dependency should reduce irreversible deformation or creep at use temperatures. 34,35,71 While hardly any creep behavior could be observed up to 70 °C, a slight increase in creep rate could be determined starting from 80 °C. On the other hand, when observing the creep rate as a function of temperature in Figure S16c, a reduction in deformation could be found for PA-3 compared to PA-2, which was in accordance with stressrelaxation data.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…In order to probe the long-term reactivity of these PA networks at lower temperatures, creep experiments without recovery were conducted by applying 2 kPa shear stress for 5000 s between 40 and 90 °C on PA-2 and PA-3 (Figure S16). It is known that a higher temperature dependency should reduce irreversible deformation or creep at use temperatures. ,, While hardly any creep behavior could be observed up to 70 °C, a slight increase in creep rate could be determined starting from 80 °C. On the other hand, when observing the creep rate as a function of temperature in Figure S16c, a reduction in deformation could be found for PA-3 compared to PA-2 , which was in accordance with stress-relaxation data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations